Strategi Komunikasi Tomoro Coffe Ngaliyan dalam Meningkatkan Penjualan Melalui Layanan dan Iklan Aplikasi Shopeefood - Michaell Robi Salgado; Urip Mulyadi (INDO PUBLISHING, 2025)
This research is motivated by the rapid development of the coffee industry in Indonesia, characterized by the proliferation of cafes and coffee shops. Tomoro Coffee Ngaliyan is an example of a cafe that has capitalized on this trend with a comfortable and modern concept. The aim of this study is to analyze the communication strategy implemented by Tomoro Coffee Ngaliyan to enhance sales through ShopeeFood services and advertising. This research employs a qualitative approach, utilizing interviews and secondary data analysis. The findings indicate that Tomoro Coffee applies a structured and effective marketing strategy through the Segmentation, Targeting, and Positioning (STP) approach, as well as the Stimulus-Organism-Response (SOR) model. Through engaging promotions, appealing product presentations, and fast delivery services, the company has significantly increased customer loyalty and product sales. Additionally, collaboration with popular brands, such as Jujutsu Kaisen, has proven effective in attracting a broader market interest, particularly among fans of anime and pop culture. By introducing products in collaboration with well-known characters, Tomoro Coffee has successfully created positive buzz and enhanced their brand visibility. This research is expected to serve as a valuable reference for the development of digital communication strategies in the culinary sector, as well as provide insights into the importance of innovation and collaboration in capturing consumer attention in an increasingly competitive market